Analisis Akad pada Transaksi E-Commerce dengan Metode Cash on Delivery (COD) perspektif Fikih Mu’amalah - Azimar Syamsi; Arsal Arsal (Journal of Islamic Law and Wisdom, 2025)
The e-commerce transaction payment system is not only limited to credit cards, debit cards, electronic wallets, or paylaters, but also via the COD (Cash On Delivery) method, where payment is made in cash when the goods arrive at their destination, which is handed over by the courier. Basically, in mu'amalah jurisprudence there have been studies relating to transaction rules, but in the case of e-commerce with a COD system, this has not been found in classical jurisprudence studies. Therefore, the author is interested in conducting further research on this topic, especially regarding e-commerce transaction mechanisms using the COD method and aspects of contracts from the perspective of mu'amalah jurisprudence. This research will be carried out through literature analysis with a qualitative approach. Data will be processed and analyzed using qualitative techniques, including inductive, deductive and comparative approaches. The results of this research show that the e-commerce transaction mechanism using the COD system is by opening the application, selecting goods, checking out, and inspecting the goods before making payment for the order in cash when it arrives at its destination via a courier intermediary. The position of the contract in e-commerce transactions using the COD system, from the perspective of mu'amalah jurisprudence, is that it is permissible as long as the harmony and appropriate terms and rules are met. The transaction system uses a greeting contract